2020
DOI: 10.1108/sasbe-10-2019-0142
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining community infrastructure through community-based governance (the social practice of collective design policy)

Abstract: PurposeThis paper empirically provides information on community-driven infrastructure provision through the collective efforts of community-based organizations (CBOs). It offers an insight into emerging events on community-based infrastructure procurement, scholarship and, creating gaps for new frontiers of knowledge on community development research agenda in the emerging economies. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The study found community participation as a more dominant factor in Hakahana than in Okuryangava and Otjomuise. Fakere et al [95] focused on socio-economic characteristics and community participation through self-help enterprises; Gbadegesin et al [96] focused on the community decision-making of property-owner associations, whilst Ebekozien [97] focused on community-based low-income housing. These have been studies on urban infrastructure from the authors' respective country's perspectives and not the management perspective.…”
Section: Discussion-general Issues From a Renewed Framework For Impro...mentioning
confidence: 99%
“…The study found community participation as a more dominant factor in Hakahana than in Okuryangava and Otjomuise. Fakere et al [95] focused on socio-economic characteristics and community participation through self-help enterprises; Gbadegesin et al [96] focused on the community decision-making of property-owner associations, whilst Ebekozien [97] focused on community-based low-income housing. These have been studies on urban infrastructure from the authors' respective country's perspectives and not the management perspective.…”
Section: Discussion-general Issues From a Renewed Framework For Impro...mentioning
confidence: 99%
“…However, informal sector operations and linkages with the formal sector tend to thrive on the platform of the social services provision. This can be because the level of social amenities' availability seems to determine the pace at which the scope and depth of business interactions are affected at a given point in time (Gbadegesin et al, 2020; Gyau, 2018).…”
Section: Stakeholder Input Social Services and Informal Sector Transf...mentioning
confidence: 99%